"n Proloog tot hierdie bundel: "n Unieke groep en perspektief op die Bybel en die Nuwe- Testamentiese Wetenskap - De Villiers, Pieter G. R. (HTS teologiese studies, 2008)
A prologue to this volume: A unique group and perspective on the Bible and New Testament Studies This introduction explains the motivation for and background of a unique meeting between Dutch, Flemish and Afrikaans New Testament scholars that took place in January 2008 in Stellenbosch, South Africa. The conference focused on the theme of “Violence and the New Testament”. The introductory essay explains the nature, proceedings and outcomes of the meeting. It points out the historic nature of the meeting and that the members of the conference decided to promote a regular forum where Dutch-speaking scholars from different continents (where forms of Dutch are spoken by 60 million people) can meet.